Ministry Of Religious Affairs' Innovative Strategy In Building Lumajang District As A Model Of Religious Moderation - Arifin, Zainul; Utami, Winda; Wijayanti, Berly; Pramuja, Alvin Dian (Journal of Research and Thought on Islamic Education (JRTIE), 2024)
This study aims to explore the innovative strategies of the Ministry of Religious Affairs of Lumajang district in making Lumajang a model of religious moderation, with Senduro village as the main focus. Using a qualitative approach through a case study, data was collected through in-depth interviews with Ministry of Religious Affairs officials, religious leaders, and local communities. In addition, participatory observation of moderation activities and analysis of relevant policy documents were conducted. The results show that the Ministry of Religious Affairs' programs, such as strengthening interfaith dialogue and inclusive religious education, have successfully improved harmony and tolerance in the community. However, there are challenges such as local cultural resistance and lack of resource support. Nonetheless, the implementation of these strategies has had a positive impact in strengthening interfaith relations in Senduro Village, creating a more harmonious and tolerant environment. This research is expected to contribute to the development of religious moderation policies at the local level and enrich the discourse on religious moderation in Indonesia.